LEGAL CERTAINTY OF NOTARY POSITION REGARDING AUTHORITY TO CERTIFY ELECTRONIC TRANSACTIONS - Ida Bagus Wirya Dharma; Putu Andhika Kusuma Yadnya; I Wayan Antara; I Kadek Adi Surya (NOTARIIL Jurnal Kenotariatan, 2024)
Article 15 paragraph (3) UUJN states that Notaries have other regulated authorities apart from those contained in Articles (1) and (2) which are regulated in statutory regulations. In the Elucidation to Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary Public, it is stated "What is meant by other authority regulated in statutory regulations", among other things, the authority to certify transactions carried out electronically (cyber). notary), making deeds of waqf pledges, and airplane mortgages. The author found that there is a vagueness of norms (vague van normen). This condition of norms, which is called vagueness of norms, occurs because statutory regulations are available but the formulation of the words or sentences is not clear, giving rise to multiple interpretations. The research method used is normative legal research using primary legal material sources and secondary legal material sources. Legal materials obtained from library materials are analyzed qualitatively using the deductive method of analysis. The research results obtained are that the legal position of electronic transaction certification is a function of electronic legalization of private deeds. Certification of transactions carried out electronically only refers to private deeds that are legalized by a Notary, therefore certification of electronic transactions will still be recognized in law, but the legal force in court is weakened because it is limited to private deeds only.